Physio-chemical properties of methyl red-degrading strains isolated from textile wastewater - Luong Thi Thu Huong,; Dang Mai Anh,; Nguyen Minh Thu,; Nguyen Sy, Nguyen; Ho Thi Loan,; Ho Tu Cuong, (Vietnam Journal of Science and Technology, 2022)
Methyl red (MR)-reducing strains isolated from textile wastewater were identified and tested for physio-chemical properties. The bacterial colonies picked from the mineral medium supplemented with textile wastewater were transferred onto the mineral medium containing MR for the test. Two strains, namely SYK and STXL2, demonstrating the ability of MR decolorization in the agar medium were selected and purified. The strains SYK and STXL2 incubated in the liquid mineral medium with MR were able to reduce 100 % and 95.5 % of MR after 4 days incubation, respectively. Gram staining of both strains confirmed these two isolates were gram positive. The SYK strain has white, irregular and dry colonies while the STXL2 strain has orange, opaque, circular and glossy colonies. Both strains have short rod shape of cell under SEM images. The two strains were able to grow in the media such as Luria-Bertani medium, Meat-peptone broth, and Nutrient broth. The strain SYK were able to grow quickly in the medium with maltose while the strain STXL2 used glucose as the best carbon source. Biochemical tests showed that both strains had positive reaction in Voges-Proskauer test and negative reactions in lipase, cellulose, amylase, citrate, and gelatin hydrolysis tests. The SYK strain had positive reactions in protease, urease, and ammonia tests while the STXL2 strain had positive reaction in nitrate reduction test. The sequences of 16S rNA genes identified the SYK and STXL2 strains as Streptomyces cellulosae (100 % of similarity) and Rhodococcus ruber (99 % of similarity), and registered in the GenBank via the accessing number MZ414193 and MZ414194, respectively.